Self-control Mahasiswa yang Memiliki Kebiasaan Menonton Film Porno - Safarina Fajri Arbi; Khaerul Umam; Luthfi Atmasari (Program Studi Psikologi Islam (IAIN) Kediri, 2021)
This study uses a qualitative approach to the type of phenomenological research. The subjects are 6 active students in Kediri Regency who have a habit of watching porn films and have had sexual behavior with the opposite sex. Data were taken using indepth interviews and direct observation and analyzed using qualitative descriptive data. The results of the study revealed that the six subjects had the habit of watching porn because of various factors, which are: peer environment, curiosity, and lack of sex education. Self-control that is done is thinking about self-esteem (future consequences), thinking about the feelings of parents, and getting closer to God